A novel two-stage energy management of hybrid AC/DC microgrid considering frequency security constraints. (March 2023) - Li, Zhongwen; Xie, Xiaoli; Cheng, Zhiping; Zhi, Changyi; Si, Jikai
Abstract: The increasing penetration of renewable energy in the hybrid AC/DC microgrid (MG) reduces the inertia and further threatens the frequency security. Furthermore, the stochastic and intermittent characteristics of the renewable energy challenge the optimal scheduling of MG. To deal with these issues, this paper proposes a novel two-stage energy management strategy to minimize the operating cost of the hybrid AC/DC MG while ensuring frequency security by considering the uncertainties in both the renewable energy resources (RES) and load demand. Firstly, the relation between the maximal frequency deviation and the power reserve is derived by analyzing the dynamic frequency response model. Secondly, scenario generation and scenario reduction based on Monte Carlo simulation (MCS) are carried out to simulate the unbalanced system power. Thirdly, the day-ahead scheduling stage determines the optimal power reservation of the distributed generators (DGs) for primary and secondary frequency regulation. Then, in the intraday scheduling stage, the day-ahead power reservation plan is adjusted to meet the frequency security constraints by using the real-time updated forecasting information. Finally, the proposed energy management system (EMS) is formulated and solved. The simulation results demonstrate that the proposed method can significantly reduce the operating cost, the maximal frequency deviation, and load shedding. Highlights: Novel frequency security constraint model is derived and introduced into energy schedule framework. Power reserve is optimized to enhance the frequency ability against forecast errors. Power reserve and load shedding are readjusted to ensure frequency security.